Discovery of Novel α-Aminophosphonates with Hydrazone as Potential Antiviral Agents Combined With Active Fragment and Molecular Docking - Tian, Jia; Ji, Renjing; Wang, Huan; Li, Siyu; Zhang, Guoping (Frontiers in Chemistry, 2022)
A series of novel α-aminophosphonate derivatives containing hydrazone were designed and synthesized based on active fragments. Bioassay results demonstrated that title compounds possessed good activities against tobacco mosaic virus. Among them, compounds 6a, 6g, 6i, and 6j were equivalent to the commercial antiviral agents like dufulin. On structure optimization-based molecular docking, compound 6k was synthesized and displayed excellent activity with values of 65.1% curative activity, 74.3% protective activity, and 94.3% inactivation activity, which were significantly superior to the commercial antiviral agents dufulin and ningnanmycin. Therefore, this study indicated that new lead compounds could be developed by adopting a joint strategy with active fragments and molecular docking.